Invited review: Qualitative social and human science research focusing on actors in and around dairy farming - M. Vaarst; C. Ritter; J. Saraceni; S. Roche; E. Wynands; D. Kelton; K.E. Koralesky (Journal of Dairy Science, 2024)
ABSTRACT: Qualitative research related to humans, dairy cows, calves, and farming has been published by scientists from a variety of disciplines in many journals targeting dairy science audiences. We aimed to investigate how scientific communities other than those working in dairy science describe, analyze, and discuss dairy farming, because we found it important to bring this research to the attention of dairy scientists. In total, 117 articles were identified as involving one or more qualitative research methods in relation to dairy cattle. The review brought out a wealth of perspectives, new insights, and discussions related to dairy cattle, farmers, farming, and the sector, and in relation to societal issues and food and ecological landscapes. A broad range of qualitative research methods were used, and the literature targeted issues at the animal, farm, societal, food system, and landscape levels. Some raised critical questions about existing structures, highlighted unfairness in the industry, or pointed to new potential futures and contemporary agendas. We expect that it will be inspirational and stimulating for researchers to review new sources of literature and suggest a closer interdisciplinary collaboration among researchers from different disciplines for the future development of research involving dairy cattle. Further, it could be relevant and even necessary to engage in such interaction to avoid increasing polarization around future development of the sector—for example, related to climate change or how industrialization seems to push inequity or ignore the agency of animals themselves. Exploring perspectives of farming from different angles could enrich the outcomes of future dairy research.